Brief Report: Distinct Dysregulation of the Small Leucine‐Rich Repeat Protein Family in Osteoarthritic Acetabular Labrum Compared to Articular Cartilage. Issue 2 (February 2015) - Juchtmans, Nele; Dhollander, Aad A. M.; Coudenys, Julie; Audenaert, Emmanuel A.; Pattyn, Christophe; Lambrecht, Stijn; Elewaut, Dirk
<x xml:space="preserve">Abstract</x> Objective Articular cartilage is well studied in osteoarthritis (OA). However, the role of supporting structures, such as the acetabular labrum, a sealing structure surrounding the hip joint, has been investigated much less. We recently showed that fibrochondrocytic labrum cells are metabolically active. This study was undertaken to investigate hip OA–associated changes in human acetabular labrum cells. Methods Microarray analysis was performed to compare OA labrum cells to healthy labrum cells cultured in a 3‐dimensional alginate bead system. Data were analyzed by cluster analysis using gene set enrichment analysis software and by gene list analysis using PANTHER gene family tools. Selected candidates were validated by quantitative polymerase chain reaction analysis on labrum and cartilage samples and by immunohistochemistry. The functional impacts of the genes identified were investigated by in vitro stimulation experiments in labrum cells. Results Pathway analysis revealed increased cytokine and chemokine signaling in OA labrum cells, whereas reduced extracellular matrix interactions and transforming growth factor β signaling were observed. Several genes were significantly differentially expressed in OA compared to healthy labrum. We specifically focused on 3 small leucine‐rich repeat proteins (SLRPs), osteomodulin, osteoglycin, and asporin, that appeared to be distinctly regulated in OA labrum compared to OA cartilage. SLRPs were strongly down‐regulated in OA labrum but up‐regulated in OA articular chondrocytes. Moreover, in vitro stimulation with osteomodulin increased aggrecan expression in OA labrum cells. Conclusion OA labrum fibrochondrocytes have several features similar to OA chondrocytes. However, SLRP expression seems to be differentially influenced by degeneration in OA labrum compared to cartilage, suggesting a specific role for this supporting structure in OA. The functional impact of SLRPs on labrum cells makes them interesting targets for further studies in hip OA.